A rare case of miliary blastomycosis - Laura E. Ramirez; Alexander K. Foyt; Noureldien Darwish; Llewellyn Foulke; Christian Kostowniak; Amit Chopra (Respiratory Medicine Case Reports)
Blastomycosis is a fungal infection caused by the fungi Blastomyces dermatitidis. Presentation from this infection is variable, ranging from asymptomatic cases to disseminated infection. The Capital District of New York is not traditionally considered an endemic area; however, the increasing number of reported cases suggests it may be an emerging endemic region for Blastomycosis. Thus, we present a case of pulmonary blastomycosis with a rare diffuse miliary pattern in an immunocompetent patient from CDNY. This case highlights that pulmonary blastomycosis can lead to severe disseminated infections, even in immunocompetent individuals, emphasizing the importance of heightened clinical suspicion and timely diagnosis.